A Comparison of Classical Holomorphic Dynamics and Holomorphic Semigroup Dynamics-II - Subedi, Bishnu Hari; Singh, Ajaya (The Nepali Mathematical Sciences Report, 2020)
In this paper, we prove that the escaping set of a transcendental semi group is S-forward invari-ant. We also prove that if a holomorphic semi group is a belian, then the Fatou, Julia, and escaping sets are S-completely invariant. We also investigate certain cases and conditions that the holomorphic semi group dynamics exhibits the similar dynamical behavior just like a classical holomorphic dynamics. Frequently, we also examine certain amount of connections and contrasts between classical holomorphic dynamics and holomorphic semi group dynamics.